Environmental controls on coccolithophore sizes: a record of climate change? - G. Faucher; L. T. Bach; E. Erba; U. Riebesell (2018)
There is strong evidence that climate change is affecting the physiological rates in coccolithophores. These impacts on physiology are also reflected in changing coccosphere morphology, including coccosphere and coccolith sizes. However, pinpointing the exact reasons for observed morphological changes in natural samples or the sediment record is still very difficult because environmental parameters co-vary in the ocean. It is therefore fundamental to systematically disentangle the influence of individual environmental parameters in order to improve our understanding of what drives changes in cell and coccolith sizes under natural conditions. Here, we explored coccolithophore morphological and morphometrical variations of Emiliania huxleyi, Gephyrocapsa oceanica, Coccolithus pelagicus subsp. braarudii and Pleurochrysis carterae, in response to five different environmental variables relevant to coccolithophore physiology: pCO2, irradiance, nitrate, and phosphate limitation, temperature and Ca concentrations. Changes in laboratory culture conditions result nearly consistently in variation in coccosphere, cell and/or coccoliths sizes, with distinct species-specific sensitivities. These data suggest that in addition to ocean acidification, other parameters such as light limitation and oligotrophy due to ocean stratification and warming can induce variations in coccosphere and coccolith sizes. The envisioned goal of our research is to develop morphometric proxies to reconstruct past and future environmental conditions.